Dissecting the molecular trajectory of fibroblast reprogramming to chemically induced mammary epithelial cells - Qin, Liangshan; Zhang, Dandan; Liu, Siyi; Liu, Quanhui; Liu, Mingxing; Huang, Ben (Frontiers in Cell and Developmental Biology, 2023)
Introduction: The plasticity of cell identity allows cellular reprogramming that manipulates the lineage of cells to generate the target cell types, bringing new avenues for disease modeling and autologous tailored cell therapy. Previously, we had already successfully established a technical platform for inducing fibroblast reprogramming to chemically induced mammary epithelial cells (CiMECs) by small-molecule compounds. However, exactly how the molecular mechanism driving the lineage conversion remains unknown. Methods: We employ the RNA-sequencing technology to investigate the transcriptome event during the reprogramming process and reveal the molecular mechanisms for the fate acquisition of mammary lineage. Results: The multi-step reprogramming process first overcomes multiple barriers, including the inhibition of mesenchymal characteristics, pro-inflammatory and cell death signals, and then enters an intermediate plastic state. Subsequently, the hormone and mammary development genes were rapidly activated, leading to the acquisition of the mammary program together with upregulation of the milk protein synthesis signal. Moreover, the gene network analyses reveal the potential relationship between the TGF-β signaling pathway to mammary lineage activation, and the changes in the expression of these genes may play important roles in coordinating the reprogramming process. Conclusion: Together, these findings provide critical insights into the molecular route and mechanism triggered by small-molecule compounds that induce fibroblast reprogramming into the fate of mammary epithelial cells, and they also laid a foundation for the subsequent research on the development and differentiation of mammary epithelial cells and lactation.